PENGOLAHAN SATE GURITA (Octopus sp.) di UMKM. MINA JAYA MANDIRI, PANTAI KONDANG MERAK, DESA SUMBERBENING, KECAMATAN BANTUR, KABUPATEN MALANG - Puspitasari, Yunita Eka; Rohmatuzzahro, Umi; Hardoko, Hardoko; Suprayitno, Eddy; Djamaluddin, Heder; Tambunan, Jeny Ernawati; Panjaitan, Mickhael A.P.; Chamidah, Anies (Universitas Mataram, 2024)
Satay or satay is a food that is very popular with everyone and is quite popular in Indonesia, Malaysia and Singapore. Satay can be made from beef, chicken, lamb, and seafood such as tuna and shellfish. So far, octopus in the South Malang coastal area is also found in abundance during the season and is only sold in the form of fresh octopus. UMKM Mina Jaya Mandiri intends to serve processed octopus in the form of satay, so it is collaborating with the Malang Regency Fisheries and Maritime Service and Brawijaya University universities to get training on the diversification of processed octopus, in this case octopus satay. This community service program aims to (1) provide a general overview of the processing of octopus satay (2) train fish processors at Kondang Merak Beach MSMEs to make octopus satay products using a semi-mechanical grill. This community service activity was carried out by simulating the processing of octopus satay using a semi-mechanical grill. The results of community service activities at UMKM Mina Jaya Mandiri, Kondang Merak Beach show that MSME business actors are enthusiastic about making octopus satay in their respective places of business. The application of a semi-mechanical grill in making octopus satay provides a taste that is more popular with the public and is more efficient in terms of grilling time. This can encourage MSMEs to process fresh octopus into octopus satay using mechanical grilling technology and increase business actors' income from the increasing number of tourists visiting and enjoying various seafood culinary preparations at Kondang Merak Beach.